SMS GATEWAY IMPLEMENTATION FOR CAR SPARE PARTS INVENTORY AT CV. MOL JAYA - Purnama, Laila; Helmiah, Fauriatun; Dermawan, Ari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract : CV. MOL JAYA is one of the CVs engaged in providing car spare parts. In terms of spare parts inventory processing in CV. Mol Jaya is still experiencing difficulties, such as not being able to find out the amount of spare parts stock and sales reports that are not optimal, so the cause of work is delayed because they have to wait for parts orders from suppliers. This study aims to manage inventory and speed up the work of employees in overcoming spare parts supply problems in the Warehouse. The method in this study applies Supply Chain Management as for the stages, namely by managing raw materials, production, to distribution to end consumers in the most economical and effective way. The results of this research are in the form of a web-based goods inventory gateway sms application that has been successfully built and running well, as an information system that can assist in inventory management, quantity of spare parts stock and sales reports. The application of Supply Chain Management in a web-based application is very effective for coordinating the relationship between suppliers and CV. Mol Jaya. Keywords : Inventory; Supply Chain Management; SMS gateway Abstrak : CV. MOL JAYA merupakan salah satu CV yang bergerak dibidang menyediakan barang sperepart mobil . Dalam hal pengolahan persedian sparepart di CV. Mol Jaya masih mengalami kesulitan , seperti tidak dapat mengetahui jumlah stok onderdil dan laporan penjualan kurang maksimal , sehingga penyebab pekerjaan tertunda karena harus menunggu pemesanan onderdil dari pemasok. Penelitian ini bertujuan untuk mengelola persedian barang atau inventory dan mempercepat pekerjaan karyawan dalam mengatasi permasalahan persedian sparepart di Gudang. Metode dalam penelitian ini menerapan Supply Chain Management adapun tahapannya yaitu dengan melakukan manajemen terhadap bahan baku, produksi, sampai distribusi kepada konsumen akhir dengan cara yang paling hemat dan efektif. Hasil dari penelitian ini berupa aplikasi sms gateway inventory barang berbasis web yang berhasil dibangun dan berjalan dengan baik, sebagai sistem informasi yang dapat membantu dalam pengelolaan inventory , kuantitas stock suku cadang dan laporan penjualan. Penerapan Supply Chain Management pada aplikasi berbasis web sangat efektif untuk mengkoordinasikan hubungan antara pemasok dan CV. Mol Jaya. Kata Kunci : Persediaan; Manajemen Rantai Pasokan; Gerbang SMS